A paradigm shift is necessary to relate running injury risk and footwear design - comment on Nigg et al. - Joseph Hamill; Katherine A. Boyer; Gillian Weir (Bern Open Publishing, 2018)
In this commentary, we respond to suggestions that new paradigms are needed to relate running-related injury risk and footwear design. We concur with the authors of this paper that the previous paradigms on which footwear were designed are faulty. We also concur with the authors that new paradigms are indeed needed and that research must take into consideration more epidemiological studies and more prospective biomechanical studies. The authors suggest new paradigms including muscle tuning, the preferred movement path and functional groups. However, we do raise questions about each of these suggestions regarding how these paradigms can be developed in future research designs.